Глиняні жертовники лісостепового Подніпров'я ранньоскіфського часу - Безсонова, С.С. (Археологія, 1996)
Публікуються залишки глиняних орнаментованих жертовників, ареал яких у Середньому Подніпров'ї збігається з ареалом пам'яток жаботинського етапу ранньоскіфського періоду. Головна увага приділяється питанням типології, датування та походження цих жертовників. Публикуются остатки глиняных орнаментированных жертвенников, ареал которых совпадает с ареалом памятников жаботинского этапа раннескифского периода. Приводимые среднеевропейские аналогии позволяют предполагать дополнительный культурный импульс со стороны носителей одной из культур фракийского гальштата, скорее всего группы Басарабь, возможно их переселение в Среднее Поднепровье во второй половине VIII в. до н. э. Remains of clay-made pattern-decorated credence altars are described. Their areas of distribution coincides with that of relics of the Zhabotin stage of the early Scythian period. The mid-European analogies carried out have permitted supposing an additional cultural impetus from the side of one of the cultures of the Frakian haulstate, most likely the Basarab group, their migration to the mid-Dnieper territory in the second half of the 8th cent. В. С. is quite possible.